ANALISIS LOKASI TERHADAP MINAT BELI PERUMAHAN DI KOTA TANGERANG SELATAN - Nursoleh, Mr (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
South Tangerang is an urban city with an average population growth of 3%. This opens up opportunities for the property industry. Therefore, this study was conducted to analyze people's buying interest in property in the southern city of Tangerang. The research method used is quantitative with descriptive explanation. The analysis method used is a simple linear regression analysis with a sample of 100 respondents and the sampling technique used is the saturated sample technique. The results showed the location of the house determines the purchase decision, after that the price, access and facilities. This finding confirms the fact, do not be surprised if the population of urban cities continues to increase significantly, and land prices creep up